2018
DOI: 10.1007/978-3-319-98192-5_25
|View full text |Cite
|
Sign up to set email alerts
|

A Scalable Consent, Transparency and Compliance Architecture

Abstract: Abstract. In this demo we present the SPECIAL consent, transparency and compliance system. The objective of the system is to afford data subjects more control over personal data processing and sharing, while at the same time enabling data controllers and processors to comply with consent and transparency obligations mandated by the European General Data Protection Regulation. A short promotional video can be found at https://purl.com/specialprivacy/demos/ESWC2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…SPIRIT [7], SPECIAL [8], and the work presented in [19] have concepts related to data subjects, purposes, and data processing activities that are relevant. Those vocabularies were, however, mostly developed for a posteriori compliance analysis of logs or assessing operations before their execution.…”
Section: Consent Ontology: Related and Prior Workmentioning
confidence: 99%
See 2 more Smart Citations
“…SPIRIT [7], SPECIAL [8], and the work presented in [19] have concepts related to data subjects, purposes, and data processing activities that are relevant. Those vocabularies were, however, mostly developed for a posteriori compliance analysis of logs or assessing operations before their execution.…”
Section: Consent Ontology: Related and Prior Workmentioning
confidence: 99%
“…a dictionary). Notice on line 17, we rely on strSplit function offered by Apache Jena's SPARQL processor 8 to split a string into a list. Such a function was, unfortunately, not available in SPARQL.…”
Section: Step 2: Generation Of An R2rml Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work encodes the consent collected in the past and has a representation for purposes. In [14], the authors demonstrated the SPECIAL consent, transparency and compliance system. They also used RDF for representing concepts such as purpose.…”
Section: Related Workmentioning
confidence: 99%
“…They then avail of "OWL reasoning to verify whether the authorized operations specified by a data subject through their given consent, subsume the specific data processing records in the transparency log." [14] Both studies have models for similar concept (data subject --or the person, purpose, etc.). And both studies aim to analyze compliance based on logs (thus a posteriori) and to present the results of that analysis in a dashboard.…”
Section: Related Workmentioning
confidence: 99%